Health Information for International Travel 2005 - 2006 - Arguin, Paul et. Al (Elsevier, 2005)
Here's vital pre-travel health-care recommendations and essential information on health risks abroad. It provides information on vaccination requirements, recommendations, and diseases prevention strategies for yellow fever, malaria, HIV/AIDS, cholera, hepatitis, influenza, SARS, viral hemorhagic fevers, plague, and many other illness.
Keywords: Communicable diseases; Infectious diseases; Non-Fiction